The Effects of Cetylpyridinium Chloride (Cecure® CPC Antimicrobial1) on Campylobacter Spp. on Raw Poultry:A Review - Waldroup, A.L.; Beers, K.L.; Cook, P.E.; Dell, E.A.; Odglen, R.; Baker, R.A.; Coleman, C.W.; Smith, B.A.; Maingi, B.W. (International Journal of Poultry Science, 2010)
Published findings have clearly demonstrated that between 0.1 and 0.5%, Cecure® is by far the most efficacious antimicrobial treatment available for controlling Campylobacter on poultry carcasses. Safe Foods Corporation’s commercially available pre-chill and post-chill Cecure® applications should be fully capable of meeting and exceeding any Campylobacter government regulation that will be issued, regardless of the sampling plan or specific isolation methodology that may be mandated. Safe Foods’ previous laboratory studies and in-plant experience, as well as the published findings of other scientists, suggest that Cecure® will be able to achieve at least a 1-2.5 log reduction in Campylobacter levels on pre-chill broilers, with incidence rates being reduced from 80-90% to no greater than 7-9% with a concentration of Cecure® between 0.1 and 0.5%. With a post-chill Cecure® application, the antimicrobial should virtually eliminate the organism (2-3 log reduction) with an expected incidence rate of no greater than 3-5% at a Cecure® concentration between 0.1 and 0.5%.